COVID-19 and youth sports: Psychological, developmental, and economic impacts - Sanderson, J.; Brown, K. (International Journal of Sport Communication, 2020)
COVID-19 has dramatically altered and disrupted sport in unprecedented ways, and youth sports is one sector that has been profoundly impacted. In the United States, the youth sports industry generates $19 billion dollars annually, while youth sport tourism is estimated at $9 billion annually. With youth sports at a standstill, the effect on the youth sports infrastructure is significant. The purpose of this scholarly commentary was to discuss the psychological, developmental, and economic fallout from the stoppage of youth sports that has touched millions of participants, their families, and a substantial youth sports structural system. This work also addresses the potential restructuring of youth sport megacomplexes, cascading effects of canceled seasons, likely sponsorship losses, and potential growing socioeconomic divide in participation that could result from the pandemic. Thus, there is still much uncertainty about the future of youth sport participation and subsequent adjustments that may impact established participation and consumption norms.